1971
DOI: 10.1073/pnas.68.8.1665
|View full text |Cite
|
Sign up to set email alerts
|

Specific Heterologous Enhancement of Immune Responses

Abstract: In suspension cultures of mouse spleen cells, the addition of small amounts (1-100 ng) of a heterologous antigen to which the donor mice had been primed significantly increased the number of anti-sheep erythrocyte plaques appearing after stimulation with sheep erythrocytes. A similar addition to identical cultures from unprimed donors produced a small depression in the number of such plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1972
1972
1983
1983

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…In contrast, the addition of TT to cultures with similar numbers of normal spleen cells and normal thymocytes resulted in a slight depression in the anti-SRBC response (groups 3 and 4). Addition of TT to positive control (groups 5 and 6) and negative control cultures (groups 7 and 8) resulted in significant augmentation or slight depression, respectively, of the PFC response, as previously reported (6). We obtained no anti-SRBC plaques in SRBC-stimulated cultures of primed or normal thymocytes cultured in the presence of priming antigen nor in its absence (groups 9 and 10).…”
supporting
confidence: 50%
See 3 more Smart Citations
“…In contrast, the addition of TT to cultures with similar numbers of normal spleen cells and normal thymocytes resulted in a slight depression in the anti-SRBC response (groups 3 and 4). Addition of TT to positive control (groups 5 and 6) and negative control cultures (groups 7 and 8) resulted in significant augmentation or slight depression, respectively, of the PFC response, as previously reported (6). We obtained no anti-SRBC plaques in SRBC-stimulated cultures of primed or normal thymocytes cultured in the presence of priming antigen nor in its absence (groups 9 and 10).…”
supporting
confidence: 50%
“…Recently, we reported that augmented responses similar to those after a second exposure to the same antigen need not be specific (6). Our data indicated that the addition of specific antigen to a population of primed cells results in the enhancement of the response to another unrelated antigen present in the environment.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Each culture contained 1 ml of cells (2 X 107) suspended in medium supplemented with 10% fetal bovine serum (FBS) (Reheis Chemical Co., Kankakee, Ill.). Cultures were fed daily with a nutritional supplement (13) and were stimulated with approximately 3 million SRBC on the day of culture (day 0). 1 ng of tetanus toxoid was added to half of these cultures on day 2.…”
Section: Preparation Of Spleen Callmentioning
confidence: 99%